Traces of Multicultural Education in the Mihrab Ornaments of the Great Mosque of Demak - Zairin, Achmad; Sugiarto, Eko; Haryono, Slamet; Widodo, Widodo (Universitas Negeri Semarang, 2025)
Multiculturalism, as an essential issue for humanity, has been adopted in Java, Indonesia, through the legacy of the artifacts of the Great Mosque of Demak. This is also an important marker for the basis of local education strategies. This study examines the traces of multicultural education in the Mihrab ornament of the Great Mosque of Demak and its relevance in learning fine arts. The method used is a literature study with a qualitative approach, in which various academic sources, journals, and historical studies are analyzed to understand the symbolic meaning and educational potential of the ornament. The study results indicate that the Mihrab ornament of the Great Mosque of Demak has a philosophical value that can be used as a medium for learning multicultural-based fine arts. Education integration strategies can be carried out through visual media, contextual approaches, and creative projects. With this approach, fine arts education not only functions as a means of developing artistic skills but also as a medium for instilling the values ​​of tolerance, diversity, and cultural inclusiveness. This study contributes to developing a more contextual fine arts curriculum based on local cultural heritage.